Patterns and Progress in Horticultural Farming in Rural Areas of Uttarakhand Himalaya - Sati, V. P. (Indian Journal of Hill Farming, 2018)
Uttarakhand grows a number of horticultural crops – fruits, vegetables, spices and flowers. Its patterns in terms of area, production and yield vary from crop to crop and from one district to other. The main objective of this paper was to examine patterns and progress of horticultural farming in rural areas of Uttarakhand. We gathered two time series (2001-2014) data from secondary sources and analyzed area, production and yield of crops. It was observed that although, there was an increase in crops’ yield (13.6%), area (21.1%) and production (35.5%) yet increase in yield was comparatively less than area and production, during the period.